Multi-wavelength observations and modeling of a microflare: constraining non-thermal particle acceleration - Polito, Vanessa; Peterson, Marianne; Glesener, Lindsay; Testa, Paola; Yu, Sijie; Reeves, Katharine K.; Sun, Xudong; Duncan, Jessie (Frontiers in Astronomy and Space Sciences, 2023)
In this work we analyze a small B-class flare that occurred on 29 April 2021 and was observed simultaneously by the Interface Region Imaging Spectrograph (IRIS) and the Nuclear Spectroscopic Telescope Array (NuSTAR) X-ray instrument. The IRIS observations of the ribbon of the flare show peculiar spectral characteristics that are typical signatures of energy deposition by non-thermal electrons in the lower atmosphere. The presence of the non-thermal particles is also confirmed directly by fitting the NuSTAR spectral observations. We show that, by combining IRIS and NuSTAR multi-wavelength observations from the corona to the lower atmosphere with hydrodynamic simulations using the RADYN code, we can provide strict constraints on electron-beam heated flare models. This work presents the first NuSTAR, IRIS and RADYN joint analysis of a non-thermal microflare, and presents a self-consistent picture of the flare-accelerated electrons in the corona and the chromospheric response to those electrons.